(untitled) (Journal of Bangladesh Institute of Planners, 2015)
Generation of municipal solid waste is ominously increasing due to the rapid growth of population coupled with the increasing scale of economic activity, i.e. urbanization, industrialization, and improved living standards. Urban local bodies across the world are struggling with the tenacious problems of municipal waste management, particularly in disposal of waste. Based on estimates, two Dhaka city corporations collectively generate about 1.6 million tons of municipal waste each year and emit approximately 1 million tons of GHG. This paper aims to evaluate the capacity of Dhaka North and Dhaka South City Corporations in handling waste against the mounting generation of MSW. The entire study is developed with secondary information but substantial primary information has been collected to update and to verify the information received from secondary sources. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 35-48